The Determinants of the Geographic Concentration among Immigrants: Application to Australia - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2002)
This study develops a theoretical framework for the study of the tendency for immigrant groups to be geographically concentrated. Testing the model for Australia shows that the extent of geographic concentration of immigrant groups is negatively related to age at migration, duration of residence in Australia and the proportion of the birthplace group that is fluent in English. The extent of geographic concentration is also affected by the availability of ethnic media and the distance between the country of origin and the place of residence in Australia.
Keywords: J61; J15; 330; Immigrants; geographic concentration; enclaves; Australia; Migranten; Einwanderung; Wohnstandort; Regionale Konzentration; Schätzung; Australien